Different reprogramming ability of fibroblast and cumulus cells after treated with trichostatin A for nuclear transfer - XIANGCHEN, L I; YAXIN, YAO; YONG, ZHANG; DAPENG, JIN; WANG, YIPENG; WEIJUN, GUAN; YUEHUI, M A (The Indian Journal of Animal Sciences, 2011)
Fibroblasts and cumulus cells are more prone to be reprogrammed than other cell types, and the reprogramming ability of donor cells will be improved after treated with Trichostatin A (TSA). In this study, both sheep fibroblast cells (SFCs) and sheep cumulus cells (SCCs) were treated with different concentration of TSA to investigate its influences on reprogramming ability. The motilities of SCCs were quite low when the concentration of TSA reached 25ng/ml, and 10ng/ml TSA was enough to increase the levels of histone acetylation or decrease DNA methylation significantly (P<0.05), then inhibited the proliferation of SFCs in G0/G1. Moreover, the developmental rate of the NT embryos increased when the SFCs treated with 10 ng/mL TSA (P<0.05), but an opposite result was got in the TSA-treated SCCs group. Consequently, the fibroblast cells treated with 10 ng/ml TSA are more competent as donor cells.